2007
DOI: 10.1016/j.yexmp.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-3 (stromelysin-1) in acute inflammatory tissue injury

Abstract: Mice lacking matrix metalloproteinase-3 (MMP-3; stromelysin-1) demonstrated significantly less injury than their normal counterparts following the formation of IgG-containing immune complexes in the alveolar wall or in the wall of the peritoneum. Likewise, mice lacking MMP-3 demonstrated less lung injury following intra-tracheal instillation of the chemotactic cytokine macrophage inhibitory protein-2 (MIP-2) than did mice with MMP-3. There was a relationship between tissue injury (evidenced histologically) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…Induction of genes in H37Rv-infected iNOS -/-mice with relation to oxidative burst (phagocyte oxidase phox, myeloperoxidase (MPO), xanthine dehydrogenase (XDH) [53], lymphocyte cytosolic protein 2 LCP2 [54]) and protection against oxidative stress (superoxide dismutases, peroxireduxins, metallothioneins and glutathione reductase) or other neutrophil functions such as plastin (LCP1) [55] emphasize that neutrophils and oxidative processes are prominent in H37Rv-mediated inflammation. MMP, especially MMP3 [56], MMP8 and MMP9 [57] are involved in neutrophil-mediated inflammatory processes [56,57]. These MMP were strongly induced during H37Rv-mediated inflammation in iNOS -/-lungs as well.…”
Section: Innate Immune Responsementioning
confidence: 95%
“…Induction of genes in H37Rv-infected iNOS -/-mice with relation to oxidative burst (phagocyte oxidase phox, myeloperoxidase (MPO), xanthine dehydrogenase (XDH) [53], lymphocyte cytosolic protein 2 LCP2 [54]) and protection against oxidative stress (superoxide dismutases, peroxireduxins, metallothioneins and glutathione reductase) or other neutrophil functions such as plastin (LCP1) [55] emphasize that neutrophils and oxidative processes are prominent in H37Rv-mediated inflammation. MMP, especially MMP3 [56], MMP8 and MMP9 [57] are involved in neutrophil-mediated inflammatory processes [56,57]. These MMP were strongly induced during H37Rv-mediated inflammation in iNOS -/-lungs as well.…”
Section: Innate Immune Responsementioning
confidence: 95%
“…In mice lacking MMP-3, intratracheal administration of immunoglobulin G resulted in less lung injury and neutrophil influx [55]. In another study, investigators reported a significant difference in neutrophil recruitment between MMP-3 knockout mice and MMP-9 knockout animals with the same injury, suggesting that MMP-3 plays an essential role in migration of neutrophils from the pulmonary circulation to the alveolus [52].…”
Section: Other Inhibitorsmentioning
confidence: 96%
“…Furthermore, a model of VILI [19] demonstrated that MMP-9 function is worth preserving, given that mice defi cient in this protease had increased levels of lung injury. On the other hand, MMP-3 may be detrimental, as mice lacking this MMP were protected against lung injury caused by administration of nonspecifi c IgG [20] or bleomycin [21]. Regarding MMP-8, this protease has shown diff erent eff ects depending on the experimental model.…”
Section: The Role Of Infl Ammation In Tissue Damage and Repairmentioning
confidence: 99%